Enjoymeter for Exploring Micro-Scale Changes in Foreign Language Enjoyment - Wang, Rouhua (Frontiers in Psychology, 2022)
With the popularity of positive psychology research in second language acquisitionsince 2014, foreign language enjoyment (FLE) has attracted many researchers in this domain. Several innovative quantitative and qualitative research methods have been used so far to explore foreign language enjoyment. However, given the dynamic nature of FLE, the development of innovative tools can contribute to the exploration of micro-scale dynamics of FLE. The purpose of this study is to introduce enjoymeter as one of these innovative tools and provide an example for its use in a foreign language learning setting. To do this, the function of the enjoymeter in the dynamics of FLE in an English language course in China is explained and the collected data via this tool are analyzed.